Coding Dyadic Behavior in Caregiver-Child Interaction from a Clinical Psychology Perspective: How Should Multiple Instruments and Outcomes Be Dealt with? - Anne Jung; Nina Heinrichs (MDPI AG, 2023)
The experiences children have in the interactions with their caregivers influence their developmental outcomes. To target caregiving and optimize intervention effects, the assessment of caregiver-child interactions is highly relevant for families affected by parental mental disorders. Behavioral observation is a widely used method for assessing family dynamics, and the literature offers a wide variety of instruments with which to code such data. However, a structured overview of behavioral observation instruments (BOIs) is lacking, and the multitude of types of dyadic behaviors (DBs) assessed within each BOI are complicating their application. We aim to provide an overview of the BOIs applied to families affected by mental disorders and suggest a DB taxonomy that may be used across BOIs. We first conducted a systemic literature search to identify the most frequently used BOIs and the DBs they capture in clinical psychology. Second, we asked 13 experts to sort DB terms based on perceived conceptual similarity and analyzed these results using multidimensional scaling. We found approximately 450 different terms for DBs, and we argue that DBs can be classified within two overarching dimensions, i.e., in terms of structure and in terms of reaction to a child's signals. These efforts can facilitate the coding and application of BOIs in clinical practice.